Dietary n-3 polyunsaturated fatty acid intake and all-cause and cardiovascular mortality in adults on hemodialysis: The DIET-HD multinational cohort study. Issue 1 (February 2019) - Saglimbene, Valeria M.; Wong, Germaine; Ruospo, Marinella; Palmer, Suetonia C.; Campbell, Katrina; Larsen, Vanessa Garcia; Natale, Patrizia; Teixeira-Pinto, Armando; Carrero, Juan-Jesus; Stenvinkel, Peter; Gargano, Letizia; Murgo, Angelo M.; et al.
Summary: Background & aims: Patients on hemodialysis suffer from high risk of premature death, which is largely attributed to cardiovascular disease, but interventions targeting traditional cardiovascular risk factors have made little or no difference. Long chain n-3 polyunsaturated fatty acids (n-3 PUFA) are putative candidates to reduce cardiovascular disease. Diets rich in n-3 PUFA are recommended in the general population, although their role in the hemodialysis setting is uncertain. We evaluated the association between the dietary intake of n-3 PUFA and mortality for hemodialysis patients. Methods: The DIET-HD study is a prospective cohort study (January 2014–June 2017) in 9757 adults treated with hemodialysis in Europe and South America. Dietary n-3 PUFA intake was measured at baseline using the GA 2 LEN Food Frequency Questionnaire. Adjusted Cox regression analyses clustered by country were conducted to evaluate the association of dietary n-3 PUFA intake with cardiovascular and all-cause mortality. Results: During a median follow up of 2.7 years (18, 666 person-years), 2087 deaths were recorded, including 829 attributable to cardiovascular causes. One third of the study participants consumed sufficient (at least 1.75 g/week) n-3 PUFA recommended for primary cardiovascular prevention, and less than 10% recommended for secondary prevention (7–14 g/week). Compared to patients with the lowest tertile of dietary n-3 PUFA intake (<0.37 g/week), the adjusted hazard ratios (95% confidence interval) for cardiovascular mortality for patients in the middle (0.37 to <1.8 g/week) and highest (≥1.8 g/week) tertiles of n-3 PUFA were 0.82 (0.69–0.98) and 1.03 (0.84–1.26), respectively. Corresponding adjusted hazard ratios for all-cause mortality were 0.96 (0.86–1.08) and 1.00 (0.88–1.13), respectively. Conclusions: Dietary n-3 PUFA intake was not associated with cardiovascular or all-cause mortality in patients on hemodialysis. As dietary n-3 PUFA intake was low, the possibility that n-3 PUFA supplementation might mitigate cardiovascular risk has not been excluded.